Hierarchical anti-reflective laser-induced periodic surface structures (LIPSSs) on amorphous Si films for sensing applications. Issue 25 (17th June 2020) - Dostovalov, A.; Bronnikov, K.; Korolkov, V.; Babin, S.; Mitsai, E.; Mironenko, A.; Tutov, M.; Zhang, D.; Sugioka, K.; Maksimovic, J.; Katkus, T.; Juodkazis, S.; et al.
Abstract : Unique hierarchical laser-induced periodic surface structures (LIPSSs) enable the detection of metal ions at sub-nM concentrations via surface-enhanced fluorescence. Abstract : Here, we applied direct laser-induced periodic surface structuring to drive the phase transition of amorphous silicon (a-Si) into nanocrystalline (nc) Si imprinted as regular arrangement of Si nanopillars passivated with a SiO2 layer. By varying the laser beam scanning speed at a fixed pulse energy, we successfully tailored the resulting unique surface morphology of the formed LIPSSs that change from ordered arrangement of conical protrusions to highly uniform surface gratings, where sub-wavelength scale ripples decorate the valleys between near-wavelength scale ridges. Along with the surface morphology, the nc-Si/SiO2 volume ratio can also be controlled via laser processing parameters allowing the tailoring of the optical properties of the produced textured surfaces to achieve anti-reflection performance or partial transmission in the visible spectral range. Diverse hierarchical LIPSSs can be fabricated and replicated over large-scale areas opening a pathway for various applications including optical sensors, nanoscale temperature management, and solar light harvesting. By taking advantage of good wettability, enlarged surface area and remarkable light-trapping characteristics of the produced hierarchical morphologies, we demonstrated the first LIPSS-based surface enhanced fluorescent sensor that allowed the identification of metal cations providing a sub-nM detection limit unachievable by conventional fluorescence measurements in solutions.